Adapting development: improving services to the poor - and Wild, Leni; Booth, David; Cummings, Clare; Foresti, Marta; Wales, Joseph (ODI, 2015)
On current trends, it will take decades or longer to bring basic services to the world’s most disadvantaged people. Meeting this challenge means recognising the political conditions that enable or obstruct development progress - a radical departure from the approach of the Millennium Development Goals.
Keywords: Practice